Influence of Integrated Nutrient Management Practices on Seedling Growth of Melia azedarach L. in Nursery - Sujatha, V. N.; Manjappa, K. (Indian Forester, 2015)
An experiment was conducted to know the effect of organic manures, bio-fertilizers and inorganic fertilizer on seedling growth of Melia azedarach. The growth parameters (seedling height, collar diameter, number of leaves, leaf area, root length and root-shoot ratio) and biomass parameters (fresh shoot and root, dry shoot and root and total fresh and dry shoot and root) were found maximum in vermicompost (30 g/seedling) compared to FYM (50 g/seedling). Among the bio-fertilizers, Azospirillum + PSB recorded maximum seedling height, number of leaves, leaf area, root length, fresh weight of shoot and root, dry weight of shoot and root and total fresh and dry weight compared to Azospirillum alone, PSB alone and no bio-fertilizer. Among the inorganic fertilizers, 1.0 g NPK found better in recording all the parameters compared to 0.5 g NPK and no NPK/seedling. Among the interactions of organic manures, bio-fertilizers and inorganic fertilizers, combination of vermicompost + PSB + 1.0 g NPK has recorded maximum seedling height (154.6 cm), collar diameter (8.53 mm) and leaf area (126.0 cm2), fresh root weight (20.01 g), total fresh weight (75.84 g), root dry weight (9.68 g) and total dry weight (35.43 g).